Pengukuran Efektivitas Perlindungan Hukum dalam Pengiriman Barang Berdasarkan Perspektif Konsumen Dalam Konteks Kuhd dan Kuh Perdata: Legal Protection of Consumers Using Goods Delivery Services (Ekspeditions) (International Forum of Researchers and Lecturers, 2024)
Freight can be generally defined that the carriage is a reciprocal agreement between the carrier with the sender, wherein the carrier binds itself to organize the transport of goods and or from one place to a particular destination safely, while the sender binds itself to pay the freight. Courier services and trade relationship of mutual influence. Development of trade is strongly influenced by the birth of a freight forwarder. Courier services also participate in the growth of foreign and domestic trade. Formulation of research objectives are a reflection direction and elaboration of strategies to problems that arise in the writing, while the writing is being implemented not deviated from its original purpose. Then formulated the goal of this paper was to determine the legal protection and implementation of consumer redress against the freight forwarder.The method used in this research is the method of empirical juridical approach. While the research is descriptive specification anaitisyang intended to describe the legislation in force associated with legal theories.Based on research that shows that in this case about liability if anything happens to the item before reaching the destination or delay in delivery or if there are other things, the company is obliged to replace losses caused his company. and in case of loss or serious damage, the company will provide compensation in accordance with the price of goods or conducted negotiations regarding the compensation agreements.